The Use of Artificial Intelligence for Primary School Mathematics: A Bibliometric Analysis - Salido, Achmad; Haryanto; Kenedi, Ary Kiswanto; Agustiana Putri , Dya Ayu (International Journal of Theory and Application in Elementary and Secondary School Education, 2024)
The role of technology, particularly artificial intelligence, in the increasingly advanced digital age has the potential to revolutionize the educational landscape in unprecedented ways. This study aims to analyze and elucidate trends related to the utilization of artificial intelligence in mathematics activities within primary schools, as well as to uncover potential research opportunities for the future. Articles for this study were retrieved from the Scopus database using the search string "artificial intelligence" AND (mathematics OR mathematical) AND ("primary education" OR "elementary education" OR "primary school" OR "elementary school"). Article analysis was conducted using Harzing's Publish or Perish and VOSviewer. The study's findings indicate that the topic of artificial intelligence and primary school mathematics has been investigated from 1974 to 2023, with a total of 66 articles published in the Scopus database. The year 2022 witnessed the highest number of publications, with 17 articles published from 1974 to October 2023. Mapping the results revealed 36 keyword items grouped into 5 clusters. In conclusion, the findings of this bibliometric analysis suggest that there is potential for further scholarly exploration on the topic of utilizing artificial intelligence in mathematics education within primary schools.